2020
DOI: 10.1038/s41467-020-19197-8
|View full text |Cite
|
Sign up to set email alerts
|

Modeling early stage atherosclerosis in a primary human vascular microphysiological system

Abstract: Novel atherosclerosis models are needed to guide clinical therapy. Here, we report an in vitro model of early atherosclerosis by fabricating and perfusing multi-layer arteriole-scale human tissue-engineered blood vessels (TEBVs) by plastic compression. TEBVs maintain mechanical strength, vasoactivity, and nitric oxide (NO) production for at least 4 weeks. Perfusion of TEBVs at a physiological shear stress with enzyme-modified low-density-lipoprotein (eLDL) with or without TNFα promotes monocyte accumulation, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 71 publications
1
51
0
Order By: Relevance
“…Moreover, analysis of the biomechanical integrity of the aorta has provided insight into optimal medical therapy for patients with a rare autosomal-dominant connective tissue disorder. 31 Novel engineering approaches were also used to generate endothelialized arteriole-scale blood vessels 32 and organoids 33 that might be used to test new therapeutics. Palikuqi and colleagues 33 achieved this by transient reactivation of E twenty-six (ETS) variant transcription factor 2 (ETV2), that is normally restricted to embryonic development of the vascular endothelium, in mature human endothelial cells.…”
Section: Vascular Mechanicsmentioning
confidence: 99%
“…Moreover, analysis of the biomechanical integrity of the aorta has provided insight into optimal medical therapy for patients with a rare autosomal-dominant connective tissue disorder. 31 Novel engineering approaches were also used to generate endothelialized arteriole-scale blood vessels 32 and organoids 33 that might be used to test new therapeutics. Palikuqi and colleagues 33 achieved this by transient reactivation of E twenty-six (ETS) variant transcription factor 2 (ETV2), that is normally restricted to embryonic development of the vascular endothelium, in mature human endothelial cells.…”
Section: Vascular Mechanicsmentioning
confidence: 99%
“…Tissue chips have also incorporated 3D culture to better mimic the spatial dimensionality of native tissues. For example, Zhang et al (2020) developed arteriole-sized tissue engineered vascular grafts in the shape of hollow conduits in the presence of physiological shear stress (Figure 1A). For over 4 weeks, the authors demonstrated that the vascular grafts possessed mechanical strength, vasoactivity, and nitric oxide production.…”
Section: Three-dimensionalitymentioning
confidence: 99%
“…In addition, vascular chips are also useful for modeling aspects of atherosclerosis. Tissue engineered blood vessels (1 mm OD, 1 cm length) were fabricated in a perfusion system to model earlystage atherosclerosis (Figures 1A,B; Zhang et al, 2020). The size of the engineered blood vessel was significantly larger compared to microfluidic approaches, which allowed for assessment of macro-scale properties such as vasoconstriction.…”
Section: Vascular Tissue Chipsmentioning
confidence: 99%
“…To fabricate a TEBV, smooth muscle cells are mixed with ECM gel (collagen, fibrin, etc.) 49 or cultured for a long period to form a dense cell sheet 50 and then shaped to a tubular structure as tunica media. To endothelialize TEBVs, the inner lumen of the tubular structure formed by SMCs is filled with EC suspension.…”
Section: Introductionmentioning
confidence: 99%